2009
DOI: 10.1007/s10681-009-0041-2
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of a novel tomato mutant resistant to the weedy parasites Orobanche and Phelipanche spp.

Abstract: Orobanche and Phelipanche, commonly known as broomrape, are dicotyledonous holoparasitic flowering plants that cause heavy economic losses in a wide variety of plant species. Breeding for Orobanche resistance is still one of the most effective management strategies for this weed. However, previous efforts to find broomrape-resistant tomato (Solanum lycopersicon) genotypes have been unsuccessful. Here, we report on the isolation and characterization of a fast-neutron-mutagenized M-82 tomato mutant, Sl-ORT1. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
32
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 50 publications
(38 citation statements)
references
References 28 publications
2
32
0
Order By: Relevance
“…These findings are consistent with Kasrawi & Abu-Irmaileh (1989), Qasem & Kasrawi (1995), El-Halmouch et al (2006), Dor et al, (2010) and Mariam & Suwanketnikom (2004), who reported acceptable tomato resistance to Orobanche.…”
Section: Resultssupporting
confidence: 89%
See 2 more Smart Citations
“…These findings are consistent with Kasrawi & Abu-Irmaileh (1989), Qasem & Kasrawi (1995), El-Halmouch et al (2006), Dor et al, (2010) and Mariam & Suwanketnikom (2004), who reported acceptable tomato resistance to Orobanche.…”
Section: Resultssupporting
confidence: 89%
“…The number of emerged spikes per host plant is considered to be an important index (Rubiales et al, 2003;Dor et al, 2010). Results showed that tomato varieties based on the number of Orobanche emerged spikes per host plant can be arranged in 5 groups.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Mashiguchi and co-workers found that light-signaling-related genes are induced in Arabidopsis seedlings shortly (90 min) following exposure to GR24. 48 Analysis of roots and shoots of WT tomato plants and of the SLs-deficient tomato mutant Sl-ORT1 49,50 suggested that SLs are positive regulators of plant light harvesting. This was deduced from the list of genes induced by GR24, following 24 to 48 h of GR24 treatment, which was enriched in genes putatively associated with light harvesting.…”
Section: Strigolactones Affect Shoot Developmentmentioning
confidence: 99%
“…An alternative and/or complementary approach for the control of Phelipanche spp. in plants is through genetic improvements or selection, and the use of new plant genotypes that are resistant to these parasites (Dor et al, 2010;Gressel, 2013).…”
Section: Introductionmentioning
confidence: 99%